2022
DOI: 10.1057/s41599-022-01435-7
|View full text |Cite
|
Sign up to set email alerts
|

Biopolitics of othering during the COVID-19 pandemic

Abstract: The COVID-19 pandemic as a global threat caused the introduction of different biopolitical measures accompanied by discourses on otherness, including xenophobic, racist, nationalist, or new orientalist discourses. The aim of this research is to map discourses on otherness during the COVID-19 pandemic. Our general hypothesis is that, despite the differences in social and cultural contexts, discourses on otherness generated during the pandemic legitimized biopolitical actions and/or measures in addition to exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…During COVID-19 worldwide, biopolitics gave rise to ethical tensions, and in response, to feelings of powerlessness, which generated scapegoating or 'othering', evidenced by rising events and experiences of racism (i.e., inherent superiority based on racialized status and cultural differences) and xenophobia (i.e., fear of foreigners) (Risti c & Marinkovi c, 2022). These were reproduced in social media and applied to immigrants and refugees to legitimize biopolitical actions and/or measures against 'foreign entities', irrespective of whether or not these impinged on self-determined freedoms, and health citizenship rights (Gover, Harper, & Langton, 2020;Risti c & Marinkovi c, 2022). Specifically, tensions were from a public communal struggle to bodily express oneself as a part of the solution 'flattening the curve' (e.g., staying home, physical distancing in public spaces, limiting travel), versus a private experience of 'othering', when one's will to health was impinged by their identification with a marginalized community (e.g., one with a 'sick' body, engaged in essential, yet devalued, domestic labour, or due to physical confines of limited space, whether at work or home).…”
Section: Biopolitics Of Health Citizenship During Covid-19 (2020)mentioning
confidence: 99%
See 1 more Smart Citation
“…During COVID-19 worldwide, biopolitics gave rise to ethical tensions, and in response, to feelings of powerlessness, which generated scapegoating or 'othering', evidenced by rising events and experiences of racism (i.e., inherent superiority based on racialized status and cultural differences) and xenophobia (i.e., fear of foreigners) (Risti c & Marinkovi c, 2022). These were reproduced in social media and applied to immigrants and refugees to legitimize biopolitical actions and/or measures against 'foreign entities', irrespective of whether or not these impinged on self-determined freedoms, and health citizenship rights (Gover, Harper, & Langton, 2020;Risti c & Marinkovi c, 2022). Specifically, tensions were from a public communal struggle to bodily express oneself as a part of the solution 'flattening the curve' (e.g., staying home, physical distancing in public spaces, limiting travel), versus a private experience of 'othering', when one's will to health was impinged by their identification with a marginalized community (e.g., one with a 'sick' body, engaged in essential, yet devalued, domestic labour, or due to physical confines of limited space, whether at work or home).…”
Section: Biopolitics Of Health Citizenship During Covid-19 (2020)mentioning
confidence: 99%
“…We drew on ‘the biopolitics of othering’ as a ‘series of complex social practices’ that demarcates ‘how one actively identifies with social boundaries’ as an ‘a priori ingredient’ to ‘processes of group dynamics and identity formation’ (Ristić & Marinković, 2022, p. 2). Ristić and Marinković's (2022) qualitative study of 27 academic articles during 2020/2021 of the COVID‐19 pandemic found that the social and political arenas during COVID‐19 constructed discourses of ‘Othering’ to make sense of the spread of the virus, including in Canada, ‘Virus‐as‐Other, lower socio‐economic groups, and migrant workers/strangers’. This study concluded that a global need to find stereotypical ‘villains’ played out in the everyday ‘politics of naming’ others for the cause of COVID‐19; this was reflected in political discourse of the ‘Chinese flu’ or the ‘Wuhan virus’, depending on the social and cultural context (Ristić & Marinković, 2022).…”
Section: Biopolitics Of Health Citizenship During Covid‐19 (2020)mentioning
confidence: 99%
“…Owing to the ubiquity of new media and digital technologies, COVID-racism has been remarkable in the speed and extent of its global spread (Depoux et al, 2020 ; Dionne and Turkmen 2020 ). Specifically, media had an important role in encouraging scapegoating and Othering (Ristic and Marinkovic 2022 ), circulating anti-Chinese and anti-immigrant discourses.…”
Section: The Nature Of Racismmentioning
confidence: 99%
“…A prominent reaction was to reengage with theories bordering to philosophy and political science, such as Foucauldian thoughts and theories of biopolitics (i.e., Lupton 2020; Ristić & Marinković, 2022;Weinfurter 2023) in which also the scholarly work of Agamben was re-evaluated (i.e., Delanty 2020). However, there was a back catalogue of relevant theories that proved pertinent as well.…”
Section: Reflection 3: Fast-track Sociology and Theorymentioning
confidence: 99%